2013
DOI: 10.4103/0972-5229.118416
|View full text |Cite
|
Sign up to set email alerts
|

Association of biofilm production with multidrug resistance among clinical isolates of Acinetobacter baumannii and Pseudomonas aeruginosa from intensive care unit

Abstract: Background and Aims:Given choice, bacteria prefer a community-based, surface-bound colony to an individual existence. The inclination for bacteria to become surface bound is so ubiquitous in diverse ecosystems that it suggests a strong survival strategy and selective advantage for surface dwellers over their free-ranging counterparts. Virtually any surface, biotic or abiotic (animal, mineral, or vegetable) is suitable for bacterial colonization and biofilm formation. Thus, a biofilm is “a functional consortium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 15 publications
4
27
1
Order By: Relevance
“…To the best of our knowledge, the current analysis provides the first statistical data linking bacterial production of biofilms with the persistence of traumatic wound infections and corroborates earlier reports on the potential virulence of the bacterial biofilm phenotype [ 25 ]. Biofilm formation, in our analysis, was largely attributed to multidrug-resistant A. baumannii , which corresponds to a prior study reporting a statistical increase in the proportion of A. baumannii isolates that were biofilm-producing and multidrug-resistant (73%) when compared to P. aeruginosa (57%) [ 41 ]. In addition, a recent analysis utilized clinical isolates collected from patients including military personnel admitted to a U.S. MTF to evaluate biofilm formation.…”
Section: Discussionsupporting
confidence: 83%
“…To the best of our knowledge, the current analysis provides the first statistical data linking bacterial production of biofilms with the persistence of traumatic wound infections and corroborates earlier reports on the potential virulence of the bacterial biofilm phenotype [ 25 ]. Biofilm formation, in our analysis, was largely attributed to multidrug-resistant A. baumannii , which corresponds to a prior study reporting a statistical increase in the proportion of A. baumannii isolates that were biofilm-producing and multidrug-resistant (73%) when compared to P. aeruginosa (57%) [ 41 ]. In addition, a recent analysis utilized clinical isolates collected from patients including military personnel admitted to a U.S. MTF to evaluate biofilm formation.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our findings, their results provided evidence that the ability to develop biofilm may be a crucial determinant in the survival of susceptible or non-MDR bacteria. However, another study indicated a significant association between high biofilm-forming ability and high level of antibiotic resistance (7). Investigation of the relationship between biofilm-forming ability and antibiotic resistance phenotypes among A. baumannii major IC types (ICI and ICII) also exhibited such a significant relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial study. Five collection strains and widely known biofilm producers, that is, S. aureus 15981 (77-80), S. epidermidis ATCC 35984 (81)(82)(83), E. coli ATCC 25922 (84)(85)(86), P. aeruginosa ATCC 27853 (87)(88)(89), and S. maltophilia ATCC 13637 (90,91), were used. All the strains were kept frozen at Ϫ80°C until the experiments were performed.…”
Section: Methodsmentioning
confidence: 99%